Agroecological measures in meadows promote honey bee colony development and winter survival. Issue 2 (8th February 2023) - Hernandez, Julie; Varennes, Yann‐David; Aebi, Alexandre; Dietemann, Vincent; Kretzschmar, André
Abstract: The homogenization of agricultural landscapes has led to a decrease in pollinator diversity and abundance. In response to this decline, farmers have implemented agroecological measures, which, in meadows, aim at providing more floral resources. These measures are the availability of unmown floral strips, delayed mowing, and discouraging the use of the conditioner, a device known to harm insects. The aim of our study was to investigate the cascade of effects of these agroecological measures on honey bee colony development and winter survival. We (1) determined the effect of these measures on colony size during the nectar and pollen collecting season in spring and summer, (2) evaluated the effect of spring and summer colony sizes on autumn size, and (3) described the effect of colony size in autumn on winter mortality. In this study, 300 honey bee colonies were monitored over three years in three cantons of Switzerland. Colony size was defined by the numbers of brood cells and of adult workers. Honey bee colony size in summer and autumn was improved by agroecological measures on meadows and likely contributed to the increased overwintering success. This study is a first step toward the targeted identification of viable agroecological measures on temporary meadows that can be implemented to promote honey bee colonies health in the agricultural landscape.